Pengaruh Kemampuan Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi - Parama Shinta, Cokorda Istri Agung; Astrama, I Made; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
In a company, human resources have a dominant role in carrying out the company's operational activities in achieving goals. To achieve this goal, do not forget to be able to optimize the work productivity of its employees. The factors that are known to influence employee work productivity are work ability and work motivation. Therefore, this study aims to examine and explain "The Effect of Work Ability and Work Motivation on Work Productivity in the Production Department at CV. Bali Racana in Batubula, Gianyar”.The formulation in this study is to determine the effect of work ability and work motivation on work productivity partially and simultaneously on CV. Bali Plan. In this study the data collection methods used were observation, literature study, questionnaires, interviews and documentation. The population in this study are employees of CV. Racana Bali as many as 30 people. The sample used in this study was 30 respondents.